Culture and corporate governance convergence. Issue 5 (12th September 2016) - Ntongho, Rachael Ajomboh
Abstract : Purpose: This paper aims to analyse the link between culture and corporate governance. In particular, it demonstrates the impact of culture in inhibiting convergence of corporate governance. Overall, the paper provides an appraisal of corporate governance laws in stakeholder-oriented states that have endured market pressure for convergence. Design/methodology/approach: The paper utilises historical trend in analyzing changes in corporate governance regulation in six countries covering three continents with stakeholder-oriented corporate governance model to determine the effect of culture in the convergence or divergence of corporate governance. Findings: The view that corporate governance is converging towards the shareholder model largely ignores cultural differences in states. An appraisal of corporate governance rules and principles that have endured Anglo-American influence reveals a strong propensity for cultural norms to dictate areas where changes occur. This paper demonstrates nominal changes in corporate governance regulation and ideologies, as states still turn to design corporate governance rules around their cultural philosophy. The paper also reveals weak political authority for convergence vis-à-vis market forces. Practical implications: Laws are strongly embedded in the corporate philosophies of states. Thus, the market and managers need to incorporate national culture into corporate practices for effective implementation. Originality/value: Few studies have examined the effect of culture on the convergence of corporate governance regulation, especially across different countries. This study does not only analyze corporate governance in developed countries but also examines emerging nations in Africa where research on convergence is very scarce.